„Wiedza rozsypana” i dziecko w świecie hipertekstowego czytania - Michułka, Dorota (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2016)
The starting point for this discussion was the process of electronic transformations of periodicals for children and young adults, which have gradually become multifunctional web portals for many different types of users (except children and young adults, also parents, teachers, and educators). As digital resources operating on the principle of convergence, such portals have become texts of culture that are present in the cyberspace and consequently are very popular with young recipients, who are the most active group of Internet users. The study of the new quality of “reading online”, which is hypertextual reading (including children’s reading), seems to be still closely connected to literature, literary studies, and narratology. Electronic links, one of the defining features of hypertext, are also practical manifestations of the concept of intertextuality. This article considers several separate issues, such as hypertextual reading as a way of communication; as reminiscences, retrospections and returns; as a game; and as community building